2019
DOI: 10.1002/2211-5463.12585
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 2 is involved in DNA damage‐mediated cell death of human osteosarcoma cells through stimulation of the ATM/p53 pathway

Abstract: Tumor suppressor p53 is a short‐lived nuclear transcription factor, which becomes stabilized and activated in response to a wide variety of cellular stresses. Around 50% of human cancer tissues carry p53 mutations, and certain p53 mutations contribute to chemoresistance. In the present study, we found that histone deacetylase 2 ( HDAC 2) acts as a co‐activator of tumor suppressor p53 and participates in the early molecular events following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Interestingly, it was proposed that CSCs chemo-resistance is associated with their enhanced DNA damage response ( Abad et al, 2020 ). HDACs participate in the DNA damage response particularly in the early event ( Sun et al, 2019 ) and even more interestingly CDDP treatment induced HDACs in tumor cells, thus contributing to resistance and to the expansion of CSCs subpopulation ( Wang et al, 2017 ). Indeed, HDACi treatment impairs DNA repair mechanisms thus potentiating CDDP antitumor effect ( Gomez-Gonzalez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was proposed that CSCs chemo-resistance is associated with their enhanced DNA damage response ( Abad et al, 2020 ). HDACs participate in the DNA damage response particularly in the early event ( Sun et al, 2019 ) and even more interestingly CDDP treatment induced HDACs in tumor cells, thus contributing to resistance and to the expansion of CSCs subpopulation ( Wang et al, 2017 ). Indeed, HDACi treatment impairs DNA repair mechanisms thus potentiating CDDP antitumor effect ( Gomez-Gonzalez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it may be hypothesized that HDAC2 could acquire the tumor-suppressive function observed in osteosarcoma. Recently, it has been demonstrated that HDAC2 binds to tumor suppressor p53 and augments its transcriptional activity in p53-wild-type osteosarcoma cells following DNA damage, indicating that the tumor-suppressive activity of HDAC2 may be dependent, at least in part, on p53 (41). Whether the functional conversion of HDAC2 could be dependent on p53, and whether p53 could directly regulate the expression of miR-489-3p, will be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…25 Dan Sun et al demonstrated that p53-HDAC2 axis plays a vital role in the regulation of the DNA damage response and contributes to chemo-sensitivity of osteosarcoma cells. 26 Jing Li et al reported that HDAC2 could upregulate the expression of IL-6 and trigger the migration of osteosarcoma cells, implying that targeted inhibition of HDAC2/IL-6 might be a potential approach for osteosarcoma therapy. 27 In this study, by combination analysis of multiple gene expression data of osteosarcoma from GEO, TCGA and Kaplan-Meier Plotter cohorts, we demonstrated that HDAC2 was overexpressed in osteosarcoma tissues, and acted as an unfavorable marker for patients' survival.…”
Section: Discussionmentioning
confidence: 99%